Simultaneous HPLC Analysis of Asiaticoside and α-Mangostin in Nanoethosomal Carriers - Aswan, Pedro Anugerah; Maggadani, Baitha Palanggatan; Fachri, Wilzar; Iswandana, Raditya (Universitas Gadjah Mada, 2026)
The development of robust analytical methods is essential for quality control of nanoethosomal formulations containing asiaticoside and α-mangostin, bioactive compounds with anti-inflammatory and antioxidant properties. Simultaneous quantification within nanocarriers is challenging and requires validated techniques. This study established a precise HPLC method, in accordance with ICH Q2(R2) guidelines, for the concurrent determination of both compounds. The technique demonstrated excellent linearity (R2 > 0.999), precision (%RSD < 2%), and accuracy (95–105% recovery). The nanoethosomal system also achieved high encapsulation efficiencies of 94.76% for asiaticoside and 99.27% for α-mangostin. This validated method provides a reliable tool for standardizing these complex nano-formulations, supporting their further development and clinical translation.